Avoiding War, Making Peace - Lebow, Richard Ned (Springer International Publishing, 2018)
'Ned Lebow is one of the most energetic, challenging and innovative writers on international relations. His arguments are always original and thought provoking.' -Sir Lawrence Freedman, Emeritus Professor of War Studies, King's College London, UK 'Ned Lebow is one of the greatest IR scholars of the last half century, and some of his greatest contributions have been to our understanding of how best to manage and prevent international crises and conflicts' -Jacques Hymans, Associate Professor of International Relations, University of Southern California, USA This book recapitulates and extends Ned Lebow's decades' long research on conflict management and resolution. It updates his critique of conventional and nuclear deterrence, analysis of reassurance, and the conditions in which international conflicts may be amenable to resolution, or failing that, a significant reduction in tensions. This text offers a holistic approach to conflict management and resolution by exploring interactions among deterrence, reassurance, and diplomacy, and how they might most effectively be staged and combined.